P-173 Guideline for Venous ThromboEmbolism(VTE) Prophylaxis for patients admitted to hospice. (19th November 2022) - Thulavavenkateswaran, Ramesh; Tempest, Emma; Oakley, Katherine
Abstract : Venous thrombosis most commonly occurs in the 'deep veins' in the legs, thighs, or pelvis. This is known as a deep vein thrombosis (DVT). If the clot lodges in the lung a very serious condition, pulmonary embolism (PE), arises. DVT and PE are known as venous thromboembolism (VTE). The 2018 update of NICE VTE prophylaxis guidance (NG 89, 2018) for palliative care patients suggests to consider VTE prophylaxis taking into account temporary increases in thrombotic risk factors, risk of bleeding, likely life expectancy, and patient preference. VTE prophylaxis should not be offered in the last days of life. There is little evidence to support or refute routine use of VTE prophylaxis in palliative care patients. This uncertainty hinges on the following issues: Unlike hospitals, an admission to hospice may not be associated with acute change in medical condition or mobility. In general, focus of care is placed on quality of life rather than life extension. It is unclear whether VTE prophylaxis reduces symptoms if a clot does develop. We developed a guideline for VTE prophylaxis based on NICE guidance and we embedded the Phase of illness as the starting point. St.Helena guideline: All patients admitted to hospice should receive a 'risk assessment' (Department of Health. Risk assessment for venous thromboembolism. March 2010) and the 'decision making tool' should be utilised to guide patient selection. Phase of illness (Witt, de Wolf-Linder, Dawkins, Daveson, et al., [2015]) for a patient can be stable, unstable, deteriorating or dying. VTE prophylaxis should not be given to people in dying phase, stable phase with no change in their mobility status and deteriorating phase of illness with prognosis of weeks. For people with unstable phase, with deteriorating phase with months prognosis and with stable phase with reduced mobility, VTE prophylaxis should be considered by taking into account thrombosis risks, bleeding risks and patient preference. Patients are not for VTE prophylaxis if there is a bleeding risk. We developed a decision-making tool as described above with a flow chart and embedded in SystmOne.